Evaluación de la adaptabilidad de seis variedades mejoradas de arveja (pisum sativum) mediante el apoyo de investigación participativa en la parroquia Eloy Alfaro (chan y san juan) cantón Latacunga provincia de Cotopaxi - Jácome Segovia, Freddy Javier (2015)
In this research work objectives they were: to assess the adaptability of six improved peas varieties (Pisum sativum) by means of a supporting participatory research in the Eloy Alfaro Parish (Chan and San Juan) from Latacunga in the Cotopaxi province. The specific objectives: to choose the best peas’ in these villages Determine the best peas varieties for these towns. Make an economic analysis of production variety of costs and benefits of wltirate the improved peas varieties. The studied factors were: FACTOR (A) towns (Chan and San Juan) and FACTOR (B) six improved peas (Andina, Ovo, Lojanita, Blanquita, Liliana, Esmeralda) we used varieties a Design of full Blocks by Azar (DBCA) with three repetition for the variables with statistical signification we performed the Tukey test around of 5%, was calculated the Cost Benefit Rate….